STUDI PENGARUH PENAMBAHAN ROADCEL-50 TERHADAP KARAKTERISTIK CAMPURAN LAPIS TIPIS BETON ASPAL (HRS-WC) - Mashuri, Mashuri; Rahman, Rahmatang; Basri, Hamdani (Jurnal REKAYASA dan MANAJEMEN TRANSPORTASI, 2011)
Mixture resistance to permanent deformation, heavy traffic and high temperature is the object of theimportant research on pavement materials.The objective of this research is to know the effect of Roadcel-50 to the characteristics of HRS-WCmixture on 0,1%, 0,2%, 0,3% and 0,4% Roadcel-50. Characteristics of HRS-WC using Roadcel-50 that willbe compared with HRS-WC mixture without Roadcel-50. Marshall Testing Methods using to evaluatingthe characteristic of HRS-WC mixture include Stability value of mixture, Durability of mixture, Void ofmixture (VIM, VMA and VFB), Flexibility of mixture (MQ value) and Marhall Immersion value.The result of Marshall test showed that the addition 0,1% to 0,4% Roadcel-50 tend to increaseOptimum Asphalt Content and Marshall Immersion Value of HRS-WC mixture, the addition 0,1% to 0,3%tend to increase stability value of mixture. However, the addition 0,4% Roadcel-50 tend to reduces ofstability value of HRS-WC mixture. While the addition 0,1% to 0,4% Roadcel-50 to the HRS-WC tend toincrease VIM and VMA value of the mixture.Generally, Hot Rolled Sheet Wearing Course (HRS-WC) mixtures with the addition of 0,1% to 0,4%Roadcel-50 gives the best result compared to HRS-WC mixture without Roadcel-50.